2022
DOI: 10.1590/fst.38322
|View full text |Cite
|
Sign up to set email alerts
|

The antibiofilm and antibacterial effects of medicinal plant extracts on isolated sulfate-reducing bacteria from orthodontic appliances

Abstract: Sulfate-Reducing Bacteria (SRB) are a heterogeneous group of oral microflorae that cause dental caries, destructive periodontal infections, and biofilms on fixed orthodontic appliances. Plant extracts as a source of antibacterial components may have acceptable activity against SRB strains and their biofilm development. Our study aimed at determining the antibiofilm, antimicrobial efficacy, and cytotoxicity of Iran's endemic plants against pathogenic SRB. Plantago ovata, Terminalia chebula, Eugenia caryophyllat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Numerous investigations demonstrated that diverse plant products and bioactive constituents from plants possess the capacity to impede the growth and formation of bacterial biofilms while also exhibiting the capability of disintegrating pre-existing biofilms [ 14 , 15 , 16 , 17 ]. For food safety, packaging, and preservation, CEOs are affordable, environmentally beneficial, and natural substitutes for synthetic preservatives.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations demonstrated that diverse plant products and bioactive constituents from plants possess the capacity to impede the growth and formation of bacterial biofilms while also exhibiting the capability of disintegrating pre-existing biofilms [ 14 , 15 , 16 , 17 ]. For food safety, packaging, and preservation, CEOs are affordable, environmentally beneficial, and natural substitutes for synthetic preservatives.…”
Section: Introductionmentioning
confidence: 99%